2015
DOI: 10.1016/j.jtusci.2014.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Determination of total phenolic and flavonoid content, antimicrobial and antioxidant activity of a root extract of Arisaema jacquemontii Blume

Abstract: We evaluated the antioxidant and antimicrobial activity of a methanolic extract of the roots of Arisaema jacquemontii. Antioxidant activity was determined in the 1,1-diphenyl-2-picryl-hydrazyl (DPPH), nitroblue tetrazolium (NBT) and ferric reducing power tests. The extract had significant antioxidant activity in all assays, with values of 64.16 ± 0.19% in the DPPH and 62.16 ± 0.17% in the NBT assays, and reduced Fe 3+ ferricyanide complex to the ferrous form (Fe 2+ ). Antibacterial activity and minimum inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
330
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 546 publications
(374 citation statements)
references
References 25 publications
6
330
1
2
Order By: Relevance
“…In order to confirm the synthesis of total flavonoids by the endophytic fungi present in the L. sidoides and plant extract (Table 2), extracts were obtained with the solvent ethyl acetate (AcOEt) to extract compounds with recognized antimicrobial activity, such as phenols and flavonoids (Baba and Malik, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In order to confirm the synthesis of total flavonoids by the endophytic fungi present in the L. sidoides and plant extract (Table 2), extracts were obtained with the solvent ethyl acetate (AcOEt) to extract compounds with recognized antimicrobial activity, such as phenols and flavonoids (Baba and Malik, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…21 As their free radical scavenging ability is facilitated by their hydroxyl groups, the total phenolic concentration could be used as a basis for rapid screening of antioxidant activity. 22 In addition, our previous study found that Hawm Nil rice (dark purple rice) had the highest TPC when compared with other color rice and cow's milk. 6 Other research of pigment rice also reported that dark purple or black rice had high TPC compared to other color rice without fermentation.…”
Section: Lactic Acid and Alcohol Concentrationmentioning
confidence: 95%
“…Plants rich in secondary metabolites including phenolics, flavonoids and carotenoids have antioxidant activity due to their redox properties and chemical structures (Baba and Malik, 2015). Results showed that the Hawm Nil rice milk kefir had higher antioxidant activity (33.32±6.48 and 1.33±0.60;%; respectively) than cow's milk kefir at 72 h Table 3.…”
Section: Antioxidant Activitiesmentioning
confidence: 98%
“…A set of reference standard solutions of rutin (25,50,75, 100 and 250 μg/ml) were prepared in the same manner as described earlier. The absorbance of test and standard solutions were determined against the blank at 510 nm using UV/Visible spectrophotometer [20] . Based on the measured absorbance, the concentration of flavonoids in the extract was read (mg/ml) from equation obtained from the Rutin calibration line and was expressed was expressed as mg of RE/g of extract.…”
Section: Total Flavonoid Content Estimation (Tfc)mentioning
confidence: 99%